The concentration of chemicals during paddy planting in Kg. Wang Ulu, Perlis - Siti Sarah Sofi (Penerbit Universiti Malaysia Perlis, 2011)
Paddy is essentially important in our part of daily life. The production of paddy in Malaysia was increased every year as the population increased. Perlis is one of the states that produce paddy because a lot of the swampy area in Perlis. This research actually concern about the concentration of chemicals that presented in water in paddy planting area. The concentration of chemicals is due to the fertilizer and pesticides been used during the paddy planting process that will flow out to the surrounding area such as canal, lakes and rivers. Hence, the concentration of chemicals in the water will affect the quality of water. The method used to determine the concentration of chemicals is standard methods for most of parameters in this research. The concentration of ammonia nitrogen (NH3-N) was determined higher at the bottom level at all of cross section of water sample. The concentration of PO43- was increased as the depth of water increased. The presented of PO43- and (NH3-N) concentration in water due to the fertilizers used increased. The presented of PO43- and (NH3-N) concentration in water due to the fertilizers used all cross section at different depth which impacted by paddy agricultural activity. The concentration of heavy metals which is Manganese (Mn), Ferum (Fe), and Zinc (Zn) indicate the negative which means the sample not present that kind of heavy metals. Besides, the concentration of (Cadmium) Cd and (Chromium) Cr present in water showed the lower concentration which affected by pesticides used to control the destructive insects.